Why Teachers Integrate YPAR in Their Teaching: Cultivating Youth Wellbeing, Student Voice, and Social Justice (LEARNing Landscapes, 2024)
In this article, the authors share what they learned from considering a collection of narrative reflections written by six high school educators, all co-authors, who have integrated youth participatory action research (YPAR) into their instructional practice. Taken together, the written reflections shed light on teachers’ reasons not only for pursuing YPAR but also for persisting with YPAR in their particular school context. The authors found that all teachers shared a commitment to social justice, yet their individual purposes for engaging with YPAR varied. Drawing on the teachers’ written reflections, the authors delve into teachers’ motivations for integrating YPAR into their teaching practice in order to conceptualize teachers’ reasons for facilitating YPAR in school.
Keywords: teacher research; YPAR; youth voice; social justice; high school; youth participatory action research